On the Bodily Basis of Human Cognition: A Philosophical Perspective on Embodiment - Gupta, Amitabha Das (Frontiers in Human Neuroscience, 2021)
This paper seeks to show that human cognition cannot be characterised purely in mentalistic term. It has a bodily basis and cognition is thus the product of the interplay between mind, body, and brain. This is how the idea of embodiment and its importance is realised and gets its foothold in both philosophy and cognitive science. This brings a radical change introducing a new framework for philosophy and cognitive science. In this new change philosophy and cognitive science have a special role to play which this paper seeks to explore. Philosophy in its capacity as a conceptual inquiry provides justification for human embodiment on a conceptual ground whereas cognitive science provides the same on an empirical and experimental ground. This brings the two disciplines closer resulting into a new field of inquiry which can be best described as the interface between philosophy and cognitive science. An important consequence that follows from this alignment is that the traditional epistemological distinction between the a priori and the empirical can no longer be rigidly maintained.